Strategies to develop an LGBTQIA+-inclusive adolescent sexual health program evaluation - Balén, Zabryna; Pliskin, Emma; Cook, Elizabeth; Manlove, Jennifer; Steiner, Riley; Cervantes, Marisa; Garrido, Milagros; Nuñez-Eddy, Claudia; Day, Maeve (Frontiers in Reproductive Health, 2024)
Introduction Adolescent sexual health interventions are increasingly incorporating content that is inclusive of LGBTQIA+ youth (lesbian, gay, bisexual, transgender, queer/questioning, intersex, asexual, and other marginalized sexualities and genders). Evaluations of such programs must also be inclusive to enhance the validity of evaluation results and avoid further marginalization. We present strategies for increasing LGBTQIA+-inclusivity based on our evaluation of SafeSpace, a sexual health curriculum. Methods To design an LGBTQIA+-inclusive program evaluation, we leveraged LGBTQIA+ research staff’s insights, pursued a parental consent waiver, developed an inclusive recruitment plan, and crafted demographic and sexual behavior survey measures with input from youth and equity experts. We conducted a pilot study with 42 youth ages 14–17 to assess the feasibility and efficacy of our strategies. Results We obtained a parental consent waiver and recruited a majority LGBTQIA+ pilot study sample (62%). Using themes from cognitive interviews with youth and experts regarding inclusive framing and use of plain language, we refined demographic measures and expanded sexual behavior measures. Conclusion Findings suggest that the strategies used to enhance LGBTQIA+-inclusivity in our evaluation of SafeSpace were effective in respectfully and more accurately capturing a fuller range of experiences and identities of LGBTQIA+ and cis-straight youth. The strategies and survey measures developed for this study can be applied to increase LGBTQIA+-inclusivity in other adolescent sexual health program evaluations.